2019
DOI: 10.1186/s12944-019-1085-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Omentin rs2274907 and FTO rs9939609 gene polymorphisms with insulin resistance in Iranian individuals with newly diagnosed type 2 diabetes

Abstract: Background Insulin resistance (IR) and fat accumulation in visceral adipose tissue are key players in developing type 2 diabetes (T2D). Several adipose tissue derived-gene polymorphisms are related to higher body mass index (BMI), insulin resistance and T2D. The association of omentin rs2274907 (Val109Asp) and fat-mass and obesity-associated (FTO) rs9939609 gene polymorphisms with overweight/obesity and T2D is controversial. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…At the genetic level, we genotyped rs12409609, a genetic variant located in the downstream regulatory region of omentin and that is in complete linkage disequilibrium with rs2274907, a missense polymorphism of the gene previously associated with CV risk [18][19][20] . In our study we did not observe any relationship between rs12409609 and axSpA nor with subclinical atherosclerosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the genetic level, we genotyped rs12409609, a genetic variant located in the downstream regulatory region of omentin and that is in complete linkage disequilibrium with rs2274907, a missense polymorphism of the gene previously associated with CV risk [18][19][20] . In our study we did not observe any relationship between rs12409609 and axSpA nor with subclinical atherosclerosis in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bonder MJ had undergone the genome-wide analysis that for the association between common SNPs (minor allele frequency (MAF) > 0.05) and microbial taxonomy, and identi ed associations of 9 loci with microbial taxonomies and 33 Loci with microbial pathways [4]. Study in Iranian individuals reported the association of omentin rs2274907 gene polymorphisms with insulin resistance in with newly diagnosed type 2 diabetes [22]. But we didn't nd the difference of omentin rs2274907 gene polymorphisms between Uyghur T2DM and healthy normal group.…”
Section: Discussionmentioning
confidence: 99%
“…The FTO gene encodes the protein that participates in energy metabolism, oxidative reactions and the metabolism of fatty acids. rs9939609 (Figure 33) is associated with an increase in the body mass index (BMI) and obesity [91,92]. The excessive expression of FTO is associated with a higher food intake and subsequent increases in body weight and fat, assuming that the level of energy expenditure and physical activity remain unchanged [93].…”
Section: Genes Responsible For Eating Preferencesmentioning
confidence: 99%